Design And Study Of Spinning Sea Wave Point Absorber - Oon, Bee Mun (Universiti Sains Malaysia, 2019)
The point absorber is a type of Wave Energy Converter (WEC) that is used to harness wave energy and convert it into useful electrical energy. It consists of a buoy, which acts as the primary converter the process of energy conversion. The waves drive the buoy and the wave energy absorbed by the buoy is converted into other form of energy through a Power Take-Off (PTO) system. Over the past few decades, there are various type of PTO mechanisms being implemented in the point absorbers such as hydraulic converter or the direct electrical drive system. None of these studies is related to the utilization of spiral drive mechanism. The main interest of this project is to study the feasibility of spinning point absorber that uses spiral drive mechanism as its PTO system. In spiral drive mechanism, the linear heaving motion of buoy is converted into rotational motion through a spiral gear and twisting shaft. A prototype with scale 1:50 has been designed, fabricated and tested in a wave tank in the laboratory. The prototype comes with five sets of twisting shaft, each with different lead angles and 3 sets of flywheel, each with different thicknesses. The twisting shafts are designed and fabricated in lead angle of 45°, 50°, 55°, 60° and 65°. The flywheels are designed and fabricated in thickness of 3mm, 6mm and 9mm. Through experiment, the most effective lead angle and thickness of flywheel are determined. Based on the results, it is found that the spinning point absorber shows optimum result when the twisting shaft with lead angle 55° and flywheel with thickness of 9mm are used. It is able to store of 4.6mJ kinetic energy, which is equivalent to 33.2% of efficiency.